Value of real-time tissue elastography for squamous cell carcinoma of the tongue. (2016) - Aktar, Dilruba; Tomioka, Hirofumi; Hirai, Hideaki; Oikawa, Yu; Mochizuki, Yumi; Shimamoto, Hiroaki; Harada, Hiroyuki
No abstract available